Federal tax autonomy and the limits of cooperation; Föderale Steuerautonomie und die Grenzen der Kooperation - Sebastian G. Kessing; Kai A. Konrad; Christos Kotsogiannis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
We consider the hold-up problem between a foreign direct investor and the government(s) in a host country with weak governmental structure and lack of power to commit. Using Nash threats, we show that an efficient investment level can be sustained for a sufficiently high discount factor and ask whether a federal structure makes collusion more or less sustainable. We show that collusion between the government and the investor is easier to sustain if the host country is more centralized or if the government layers can commit to fixed sharing rules. – – Wir betrachten das ,,Hold-up Problem“, das in den Beziehungen zwischen einem ausländischen Investor und der Regierung, bzw. den Regierungen eines Gastlandes mit schwachen institutionellen Strukturen besteht. Unter Verwendung von Nash-Drohungen wird gezeigt, dass eine Überwindung des Holdup Problems durch wiederholte Interaktion zwischen den Akteuren möglich ist. Weiterhin wird untersucht, ob föderale Strukturen eine solche Überwindung wahrscheinlicher machen oder nicht. Schließlich wird gezeigt, dass eine Überwindung des Hold-up Problems besser gelingt, wenn die verschiedenen Regierungsebenen des Gastlandes sich bindend auf eine gemeinschaftssteuerliche Aufteilung des Steueraufkommens festlegen können.
Keywords: H11; H71; H73; H77; 330; Tacit collusion; foreign direct investment; hold-up problem; federalism; vertical tax externality; tax competition